Expression of Bcl-2 marker in premalignant lesions of cervical cancer - Kamaraddi, Shreedevi; U., Ashwini Nayak; Honnappa, Shridhar; Swarup, Asha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: Cervical cancer is one of the most common gynecological cancers in women of developing countries. HPV DNA testing is preferred cervical screening method for woman 30-65 years old as HPV is the proved causative agent of cervical carcinoma. Due to the high costs involved in doing HPV DNA test there is a need for a biomarker such as Bcl-2 which can indicate the initiation of carcinogenic process of HPV infection and thus can be used to identify those woman who will need more surveillance. Methods: Specimens of cervical biopsy retrieved from incident cases for routine histopathological evaluation from the Department of Obstetrics and gynecology, M.S. Ramaiah hospital, Bangalore, India from March 2013 to September 2015 formed the source of data for the study. Results: In this study total of 46 cases were studied which included 9 cases of CIN-1, 8 cases of CIN-2, 7 cases of CIN-3, 12 cases of squamous cell carcinoma and 10 cases of on specific cervicitis. Higher number of malignant lesions (75%) expressed Bcl-2 positivity as compared to premalignant lesions (62.5%). In case of CIN lesions, Bcl-2 positivity increased as the grade increased (CIN-1- 55.56%; CIN-2 - 62.5%; CIN-3 -71.43%). Conclusions: Bcl-2 which is an intracellular membrane protein which prevents apoptotic cell death can be used as a biomarker to know the severity of the CIN lesion and hence help in identifying the high risk CIN lesions which need further surveillance and treatment.